The quality of the outputs of higher education under the LMD system - Talhi, Fatima Al-Zahra (Arab Journal for Sciences and Research Publishing, 2015)
Represents higher education the most important pillars of the development of human societies and the advancement of tools and that what occupies the position in creating and preparing technical and scientific frameworks eligible to achieve economic and social development. In addition to its role in knowledge, science and publication industry, though the adoption of quality systems in university education is only a response to the requirements of society and stimulate innovation and scientific research to achieve the sustainable development of the service of the human community.Aim of our research that shed light on one of the most important university education system components' outputs', and the aim is to measure the quality of higher education outputs and identify strengths and weaknesses.
Keywords: quality; higher education; labor market; Algerian university; LMD system